Penerapan Metode Traffic Light Reflection untuk Melatih Kemampuan Refleksi Diri dan Keterampilan Menulis Peserta Didik Sekolah Dasar: Application of the Traffic Light Reflection Method to Train Skills Self-Reflection and Writing Skills of Elementary School Students - Tri Lestari, Dewi; Tri Wahyuni, Yeni; Anggraini, Ade Eka; Dewi, Radeni Sukma Indra (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2024)
Writing skills in elementary school are activities that encourage students to develop their academic and cognitive abilities. For this reason, it is necessary to apply a method that is able to provide a significant impact. For example, by applying the Traffic Light Reflection method. The aim of this research is to determine the phenomena that occur in research subjects holistically, namely by describing the conditions encountered when applying the Traffic Light Reflection method to train self-reflection abilities and writing skills. This study used descriptive qualitative method. The data source in this research is class IV students at SD Negeri 2 Kates, Kauman District, Tulungagung Regency. The research results show that the Traffic Light Reflection method can facilitate students to write reflections during learning and reflect on learning outcomes. The use of traffic light color analogies is easy for students to understand so that students do not find it difficult to fill in the reflection sheet. Applying this method, students can evaluate and assess themselves.